Association between very to moderate preterm births, lung function deficits, and COPD at age 53 years: analysis of a prospective cohort study. Issue 5 (May 2022) - Bui, Dinh S; Perret, Jennifer L; Walters, E Haydn; Lodge, Caroline J; Bowatte, Gayan; Hamilton, Garun S; Thompson, Bruce R; Frith, Peter; Erbas, Bircan; Thomas, Paul S; Johns, David P; Wood-Baker, Richard; et al.
Summary: Background: Prematurity has been linked to reduced lung function up to age 33 years, but its long-term effects on lung function and chronic obstructive pulmonary disease (COPD) are unknown. To address this question, we investigated associations between prematurity, lung function, and COPD in the sixth decade of life using data from the Tasmanian Longitudinal Health Study (TAHS). Methods: Data were analysed from 1445 participants in the TAHS. Lung function was measured at 53 years of age. Gestational ages were very preterm (28 weeks to <32 weeks), moderate preterm (32 weeks to <34 weeks), late preterm (34 weeks to <37 weeks) and term (≥37 weeks). Linear and logistic regression models were fitted to investigate associations of prematurity with lung function measures (FEV1, forced vital capacity [FVC], FEV1 /FVC ratio, forced expiratory flow at 25–75% of FVC [FEF25–75% ], diffusing capacity for carbon monoxide [DLCO]) and COPD (post-bronchodilator FEV1 /FVC less than the lower limit of normal), adjusting for sex, age, height, parental smoking during pregnancy, number of older siblings, maternal age at birth, and childhood socioeconomic status. Interactions with smoking and asthma were also investigated. Results: Of 3565 individuals with available data on gestational age from the TAHS cohort, 1445 (41%) participants were included in this study, 740 (51%) of whom were female. Compared with term birth, very to moderate preterm birth was significantly associated with an increased risk of COPD at age 53 years (odds ratio 2·9 [95% CI 1·1–7·7]). Very-to-moderate preterm birth was also associated with lower post-bronchodilator FEV1 /FVC ratio (beta-coefficient –2·9% [95% CI –4·9 to –0·81]), FEV1 (−190 mL [–339 to –40]), DLCO (−0·55 mmol/min/kPa [–0·97 to –0·13]), and FEF25–75% (−339 mL/s [–664 to –14]). The association between very-to-moderate preterm birth and FEV1 /FVC ratio was only significant among smokers (pinteraction =0·0082). Similar findings were observed for moderate preterm birth when analysed as a separate group. Compared with term birth, late preterm birth was not associated with lower FEV1 /FVC ratio or COPD. Interpretation: This is the first study to investigate the effect of prematurity on lung function into middle-age. Data show that very-to-moderate prematurity is associated with obstructive lung function deficits including COPD well into the sixth decade of life and that this effect is compounded by personal smoking. Funding: National Health and Medical Research Council (NHMRC) of Australia, European Union's Horizon 2020, The University of Melbourne, Clifford Craig Medical Research Trust of Tasmania, The Victorian, Queensland & Tasmanian Asthma Foundations, The Royal Hobart Hospital, Helen MacPherson Smith Trust, and GlaxoSmithKline.